HIGH AVAILABILITY NETWORK DESIGN UNIVERSITY CAMPUS NETWORK DENGAN MODEL HIRARKI (HIERARCHICAL NETWORK) - Sulaiman, Oris Krianto; Nasution, Khairuddin; Siregar, Dodi (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2017)
Many of the problems that occur in large-scale computer network one of the problems is a complex network design and difficult to change because the system is running, one of these problems is within the university network, as is known the number of most Internet users come from the university, therefore design or reliable network design is required for good access at the university. Hierarchical network model is one of the efficient network design to be applied in large-scale networks. This model uses 3 layers (layer) namely core layer, distribution layer and access layer. Each layer will be maximized for use in the university network distribution layer will use inter vlan routing which will then be distributed to the faculties acting as the access layer. Network design with hierarchical model will also make it easier to monitor or monitor network traffic so it will be easy for the network administration in managing the work.